Assessment of cardiovascular risk factors among HIV-infected patients aged 50 years and older in Cameroon - Henri Olivier Tatsilong Pambou; Amandine Gagneux-Brunon; Bertrand Tatsinkou Fossi; Frederic Roche; Jessica Guyot; Elisabeth Botelho-Nevers; Caroline Dupre; Bienvenu Bongue; Celine Nguefeu Nkenfou (AIMS Press, 2022)
Background: Increasing the longevity of people living with HIV (PLHIV) around the world has been accompanied by an increase in the prevalence of cardiovascular disease (CVD) risk factors and morbidity. The impact of these trends on the epidemiology of CVD among PLHIV is less clear. The aim of this study was to assess the risk factors for CVD, and to estimate these risks at 10 years in PLHIV aged 50 and above. Methods: This was a descriptive and analytical study carried out at Mvog Ada District Hospital in Yaounde, Cameroon from January 2020 to January 2021. Descriptive bivariate analyses were used to present the data. The data are presented as frequencies and percentages for categorical variables, and in terms of means and standard deviations for continuous variables where appropriate. The 10-year CVD risk score was calculated using two tools: the validated Framingham risk score (FRS) (low < 10%, moderate 10-20% and high ≥ 20%) and SCORE score (SSC) (low < 3%, moderate 3-4% and high ≥ 5%). Multiple logistic regression models were constructed to examine the respective relationships between the binary dependent variable high CVD risk (FRS ≥ 20%) and the population group, alcohol consumption (more than 10 glasses of beer per week, or more than 35.7 cl/day) and hypertriglyceridemia (independent variables). A p-value less than or equal to 0.05 was considered statistically significant. Results: A total of 112 people aged 50 and above were enrolled in the study out of 180 people registered at the HIV care unit, that is a participation rate of 62.22%. The average age of the participants was 57.3 ± 6.4 years, and the female/male ratio was 1.6. The majority of participants (53.57%) had normal glycaemia levels (<1.10 g/L), 4.46% were diabetic and 46.40% had high blood pressure. The adherence rate for ARV treatment was 98.20%; most participants (77.20%) were alcohol consumers, and 28.10% of participants had hypertriglyceridemia. The estimates of overall cardiovascular risk in 10 years presented 50.90% of participants with low risk, 33% with moderate risk and 16.10% with high risk. Conclusions: Our study indicated an overall risk of cardiovascular events in 10 years is 16.10%, with the main conditional risk factor being hypertriglyceridemia and alcohol consumption, which appeared to triple the risk of CVD among PLHIV.